HUBUNGAN POLA KONSUMSI MAKANAN DENGAN KEJADIAN DIABETES MELLITUS TIPE II PADA LANSIA DI KELURAHAN SEI LANGKAI KOTA BATAM TAHUN 2021 - Siska Pratiwi; Regina Natalia; Made Tantra Wirakesuma; Sartika Apriani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Diabetes Mellitus (DM) is a chronic disease characterized by the body's inability to metabolize carbohydrates, fats and proteins, leading to hyperglycemia or high blood sugar levels. This study aims to determine the relationship between food consumption patterns and the incidence of type II diabetes mellitus in Sei Langkai Village, Batam City in 2021 using a cross sectional design. The sample needed in this study were 65 elderly aged 60 to 60 years and over. The measuring instrument in this study was the FFQ questionnaire and was analyzed using the Chi-Square test. The results obtained by the majority of the 65 elderly, most of the elderly had Type II DM with a fairly good food consumption pattern of 22 elderly (71.0%). The results of the bivariate analysis show that there is a significant relationship between food consumption patterns and the incidence of type II DM in the Sei Langkai subdistrict, Batam City in 2021 p value = 0.015 > α 0.05. The conclusion of the study, there is a relationship between food consumption patterns and the incidence of type II diabetes mellitus in the elderly. Suggestions are addressed to the elderly to regulate good and healthy food consumption patterns to maintain blood sugar levels within normal limits